Local Application of Non Negative Matrix Factorization Algorithm in Face Recognition - Lou Xiongwei; Huang Decai; Fang Luming; Xu Aijun (Institute of Advanced Engineering and Science, 2014)
Face recognition is a challenging issue in the field of multi-science, the main contents of the research is how to make computer have the ability of face recognition face recognition technology involved in a lot, which is a key feature extraction and classification method, this paper focuses on the study of related theory. Non-negative matrix factorization trapped MF) algorithm and local non-negative matrix factorization (LNMF) algorithm is a feature extraction method based on local features, has been successfully used in face recognition